Effect of the glucagon‐like peptide‐1 analogue liraglutide versus placebo treatment on circulating proglucagon‐derived peptides that mediate improvements in body weight, insulin secretion and action: A randomized controlled trial. Issue 2 (19th November 2020) - Kim, Sun H.; Abbasi, Fahim; Nachmanoff, Clara; Stefanakis, Konstantinos; Kumar, Ajay; Kalra, Bhanu; Savjani, Gopal; Mantzoros, Christos S.
Abstract: Aim: To examine how circulating glucagon‐like peptide‐1 (GLP‐1) concentrations during liraglutide treatment relate to its therapeutic actions on glucose and weight, and to study the effects of liraglutide on other proglucagon‐derived peptides (PGDPs), including endogenous GLP‐1, glucagon‐like peptide‐2, glucagon, oxyntomodulin, glicentin and major proglucagon fragment, which also regulate metabolic and weight control. Materials and Methods: Adults who were overweight/obese (body mass index 27‐40 kg/m 2 ) with prediabetes were randomized to liraglutide (1.8 mg/day) versus placebo for 14 weeks. We used specific assays to measure exogenous (liraglutide, GLP‐1 agonist [GLP‐1A]) and endogenous (GLP‐1E) GLP‐1, alongside five other PGDP concentrations during a mixed meal tolerance test (MMTT) completed at baseline and at week 14 (liraglutide, n = 16; placebo, n = 19). Glucose during MMTT, steady‐state plasma glucose (SSPG) concentration for insulin resistance and insulin secretion rate (ISR) were previously measured. MMTT area‐under‐the‐curve (AUC) was calculated for ISR, glucose and levels of PGDPs. Results: Participants on liraglutide versus placebo had significantly ( P ≤ .004) decreased weight (mean −3.6%, 95% CI [−5.2% to −2.1%]), SSPG (−32% [−43% to −22%]) and glucose AUC (−7.0% [−11.5% to −2.5%]) and increased ISR AUC (30% [16% to 44%]). GLP‐1A AUC at study end was significantly ( P ≤ .04) linearly associated with % decrease in weight (r = −0.54) and SSPG (r = −0.59) and increase in ISR AUC (r = 0.51) in the liraglutide group. Treatment with liraglutide significantly ( P ≤ .005) increased exogenous GLP‐1A AUC (median 310 vs. 262 pg/mL × 8 hours at baseline but decreased endogenous GLP‐1E AUC [13.1 vs. 24.2 pmol/L × 8 hours at baseline]), as well as the five other PGDPs. Decreases in the PGDPs processed in the intestines are independent of weight loss, indicating a probable direct effect of GLP‐1 receptor agonists to decrease their endogenous production in contrast to weight loss‐dependent changes in glucagon and major proglucagon fragment that are processed in pancreatic alpha cells. Conclusions: Circulating GLP‐1A concentrations, reflecting liraglutide levels, predict improvement in weight, insulin action and secretion in a linear manner. Importantly, liraglutide also downregulates other PGDPs, normalization of the levels of which may provide additional metabolic and weight loss benefits in the future.